Design and Performance Evaluation of Conventional and Modified Aerobic Composters for Food and Agricultural Waste Management - Loppies, Rasendriya Arkananta Bhanu; Febrita, Joana; Arif, Chusnul (Jurnal Teknik Sipil dan Lingkungan, 2025)
The management of organic waste, such as food scraps and straw, remains a challenge, particularly in residential areas that produce large amounts of waste but lack effective waste management systems. This study aimed to design and evaluate the performance of two types of aerobic composters: a conventional method and a modified method using a passive aeration system with perforated pipes. Six compost material variations were tested based on different ratios of food waste to straw and observed over an eight-week period using key parameters such as temperature, height, pH, moisture content, organic carbon, nitrogen content, and C/N ratio. The results showed that All compost variations met the compost quality standards of SNI 7763:2024. No significant difference was found between the conventional and modified methods based on ANOVA test results for the C/N ratio and pH. This study concluded that variation B6 was the most favorable, as it produced a C/N ratio closest to the standard value, met the quality standard criteria during the composting process, and reached acceptable pH and carbon levels more quickly than the other variations. Therefore, the compost quality of variation A2 and A3 was superior and reached maturity in a shorter time compared to the other treatments.